2006
DOI: 10.1158/1078-0432.ccr-06-0823
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Circulating Tumor Cells in Patients with Melanoma: A Systematic Review and Meta-analysis

Abstract: Background: The detection of circulating tumor cells (CTC) in patients with melanoma represents an appealing prognostic tool, but no consensus exists on this topic. We aimed to comprehensively and quantitatively summarize the evidence for the use of CTC to predict patients'clinical outcome. Methods: Fifty-three studies enrolling 5,433 patients were reviewed. Correlation of CTC status with tumor-node-metastasis disease stage and patients'overall (OS) and progression-free (PFS) survival was assessed by means of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
152
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(164 citation statements)
references
References 54 publications
8
152
0
4
Order By: Relevance
“…In other words, higher level of miRNA 200c may represent more tumor cells entering the circulation. It was documented that CTCs predict worse survival in various cancers (Mocellin et al, 2006;Rahbari et al, 2010;Wang et al, 2011;Ma et al, 2012;Zhang et al, 2012). The result of our meta-analysis could be well explained if the origin of serum miRNA 200c is CTCs.…”
Section: Discussionsupporting
confidence: 55%
“…In other words, higher level of miRNA 200c may represent more tumor cells entering the circulation. It was documented that CTCs predict worse survival in various cancers (Mocellin et al, 2006;Rahbari et al, 2010;Wang et al, 2011;Ma et al, 2012;Zhang et al, 2012). The result of our meta-analysis could be well explained if the origin of serum miRNA 200c is CTCs.…”
Section: Discussionsupporting
confidence: 55%
“…12 Heterogeneity appeared to be linked also to the use of the luminometric immuno-assay (LIA), but we could not rule out that this phenomenon was independent of the stage IV ''effect''; on the other hand, the homogeneity of hazard ratios observed with the radio-immuno-assay (RIA) was supported by only 5 series (n 5 461). Quite surprisingly, the different cutoffs used in LIA experiments did not significantly affect either S100B positivity rates or consistency of results between studies (Table II); however, as regards the latter issue, in order to yield a balanced comparison we tested only 1 trade-off value (0.15 mcg/L, the cutoff recommended by the kit manufacturers).…”
Section: Discussionmentioning
confidence: 88%
“…(ii) Standard meta-analysis methods 39,40 were applied to evaluate the overall relationship between S100B serum levels and patients' survival (meta-risk), as we have described in detail elsewhere. 12,41 Briefly, the association between S100B status (positive vs. negative, according to cutoff values determined in samples obtained from healthy subjects) and survival (overall survival, whenever available) was derived as a weighted average of study-specific estimates of the hazard ratio (HR, [observed-expected cases] S100B pos /[observed-expected cases] S100B neg ), using the inverse of variance as the weighting factor. 39,40 The natural logarithm of HR (lnHR) and the corresponding standard error (SE) were used as data points for the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses of studies identifying CTCs in breast cancer , colorectal cancer (Rahbari et al 2010) and melanoma (Mocellin et al 2006) revealed a robust prognostic value of CTCs in those tumors. Interestingly, CTCs, despite decreased in number, can be detactable in the blood long time after tumor removal, indicating that a reservoir could be present in the bone marrow, as suggested for breast cancer (Wiedswang et al 2006).…”
Section: Ctcs: Metastatic Cells Caught In the Act?mentioning
confidence: 99%